HPV-independent Vulvar Squamous Cell Carcinoma is Associated With Significantly Worse Prognosis Compared With HPV-associated Tumors. (July 2020) - Allo, Ghassan; Yap, Mei Ling; Cuartero, Julie; Milosevic, Michael; Ferguson, Sarah; Mackay, Helen; Kamel-Reid, Suzanne; Weinreb, Ilan; Ghazarian, Danny; Pintilie, Melania; Clarke, Blaise A.
Abstract : Vulvar squamous cell carcinomas (VSCC) represent the most common carcinoma of the female external genitalia, with increasing incidence. Although high-risk human papillomavirus (HPV) infection has long been implicated in the majority of cervical and anal squamous cell carcinomas, there is uncertainty about its prevalence and prognostic impact in VSCC. In this study, we conducted a retrospective integrated morphologic and multimodal HPV analysis of a cohort of 114 VSCC cases treated at the Princess Margaret Cancer Centre/University Health Network, Toronto, Canada between 2000 and 2010. VSCC histology was reviewed. We analyzed the cohort for HPV using polymerase chain reaction based method, and tissue microarray DNA and RNA in situ hybridization (ISH), and p16 immunohistochemistry. Among the 114 cases (age 70±16 yr), 36.7% of cases were classified as having histomorphology of HPV infection. HPV was detected in 31.9% (polymerase chain reaction), 14.0% (DNA ISH), and 27.3% (RNA ISH) of cases. p16 immunohistochemistry was positive in 37.8% of cases. On univariate analysis, HPV morphology ( P =0.009), p16+ ( P =0.00013), DNA ISH+ ( P =0.021), and RNA ISH+ ( P =0.00061) were associated with better 5-yr progression-free survival. DNA ISH+ ( P =0.049) was associated with better 5-yr overall survival. On multivariate analysis, HPV morphology ( P =0.033), p16+ ( P =0.01), and RNA ISH+ ( P =0.035) were associated with better 5-yr progression-free survival. In conclusion, a subset of VSCC is associated with HPV, which correlates with better outcome. Relatively inexpensive tests such as histomorphologic evaluation, p16 immunohistochemistry, and HPV RNA ISH can be used to predict outcome in VSCC. Therefore, routine reporting of HPV status in VSCC is recommended.